MAKNA SIMBOL TRADISI JHE҃҃҃҃҃҃҃҃҃NG MANTOH (Analisa Semiotika Charles Sanders Peirce - Nikmah Suryandari; Netty Dyah Kurniasari; Rose Dian J (Universitas Bunda Mulia, 2019)
ABSTRACTThis article attempts to explain Charles Sanders Peirce's semiotic analysis of the Jheng mantoh tradition symbol in Madura. The aim of this research is to find out the meaning of the symbols that exist in the Jheng mantoh tradition in Madura which began to be abandoned by the urban Madura community. The jheng mantoh tradition is one of the traditions in Madura, especially the Bangkalan region in the form of a ceremony welcoming the arrival of a daughter-in-law to the bridegroom's family. The purpose of this mantoh jheng is to establish friendship as well as to introduce the bride as a new family member to her husband's extended family. The method in this study is a qualitative descriptive approach to the triadic meaning of Charles Sanders Peirce's semiotics. The results showed that the symbols in the Jheng mantoh tradition in Madura have meanings that are loaded with the noble values of the Madurese community. The stages of Jheng Mantoh tradition are three parts, namely Jheng Mantant pre activity, Jheng Mantoh activity, and post Jheng mantoh. Each stage has its own symbol and meaning. This great jhe҃ng tradition can be found several symbols during the course of this tradition, such as binoculars, sound systems, goat heads, milk fish, tettel, various market snacks, trays, spoons, rituals of tek-tek-tek and so on.Keywords: jheng mantoh, Madura, semiotic, charles Sanders Peirce ABSTRAKArtikel ini berusaha menjelaskan tentang analisa semiotika Charles Sanders Peirce pada simbol tradisi Jheng mantoh di Madura. Tujuannya adalah untuk mengetahui makna simbol-simbol yang ada pada tradisi Jheng mantoh di madura yang mulai ditinggalkan oleh masyarakat Madura perkotaan. Tradisi jheng mantoh adalah salah satu tradisi di Madura, khususnya wilayah Bangkalan berupa upacara menyambut kedatangan menantu perempuan di keluarga mempelai laki-laki. Tujuan jheng mantoh ini adalah untuk menjalin silaturahmi sekaligus mengenalkan mempelai perempuan sebagai anggota keluarga baru kepada keluarga besar suaminya. Metode dalam penelitian ini adalah deskritif kualitatif dengan pendekatan segitiga makna semiotika charles Sanders Peirce. Hasil penelitian menunjukkan bahwa simbol-simbol dalam tradisi Jheng mantoh di Madura memiliki makna yang sarat dengan nilai-nilai luhur masyarakat Madura. Tahapan tradisi Jheng mantoh ada tiga bagian, yaitu pra kegiatan jheng mantoh, kegiatan jheng mantoh, dan pasca jheng mantoh. Masing-masing tahapan memiliki simbol dan makna tersendiri. Tradisi jhe҃ng mantoh ini dapat ditemui beberapa simbol selama berlangsungnya tradisi ini, seperti terop, sound system, kepala kambing, ikan bandeng, tettel, aneka jajanan pasar, talam, sendok, ritual tek-tek-tek dan sebagainya.Kata Kunci: jheng mantoh, Madura, semiotika Charles Sanders Peirce.